2013
DOI: 10.17503/agrivita-2013-35-1-p064-072
|View full text |Cite
|
Sign up to set email alerts
|

INFECTION PROCESS OF ENTOMOPATHOGENIC FUNGI Metarhizium anisopliae IN THE Tetranychus kanzawai (KISHIDA) (TETRANYCHIDAE: ACARINA)

Abstract: The importance of fungal attack to acarina has been observed but not yet on Tetraychus kanzawai. When infected mite, either within in a same species or even in a different species of entomopathigenic probably have similar signs and simptoms to mites.Characteristic of entomopathogenic fungus to Tetranychus kanzawai was investigated. Three selected isolates of Metarhizium aniopliae, from Philippines and Indonesia were evaluated. The following aspects were investigated: (1) Bioassay tes of virulence, (2) Koch Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…(5) Control prey (Ctrl) versus sporulating prey (Spo): The sporulating prey was a fly that underwent the vortexing protocol and, once dead, that was sporulating in a thermostatic cabinet for around 2 days (as detailed in the previous section). Before using the sporulating fly in binary choices, we checked with a binocular microscope the presence of conidiophores on the cuticle of the insect cadaver [37,38]. A total of 75 ants were tested in this condition.…”
Section: Methodsmentioning
confidence: 99%
“…(5) Control prey (Ctrl) versus sporulating prey (Spo): The sporulating prey was a fly that underwent the vortexing protocol and, once dead, that was sporulating in a thermostatic cabinet for around 2 days (as detailed in the previous section). Before using the sporulating fly in binary choices, we checked with a binocular microscope the presence of conidiophores on the cuticle of the insect cadaver [37,38]. A total of 75 ants were tested in this condition.…”
Section: Methodsmentioning
confidence: 99%
“…Mycelia and conidia from each of the three most pathogenic isolates previously identified (Sanjaya et al, 2013) were inoculated on potato dextrose agar (PDA) and single spore colony were grown on potato dextrose broth (PDB), incubated on shaker (150 rpm) at 20˚C for 5-7 days. DNA extraction was done following the manufacturer's protocol using Animal and Fungi DNA Preparation Kit (Jena Bioscience, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…RAPD has already been used to estimate the diversity of a population, for genotype characterization or constructing the molecular phylogeny of closely related taxons (Tigano-Milani et al, 1995). Previous study showed that among the seven entomopathogenic fungi isolates tested against T. kanzawai, isolates Ma4, Ma5 and Ma6 were the most pathogenic (Sanjaya et al, 2013). The objective of this research was to identify the most pathogenic fungi using RAPD technique.…”
Section: Introductionmentioning
confidence: 99%
“…Biological control is a cost‐effective and environmentally sound option for mealybug management . Native and introduced parasitic wasps, predators and entomopathogens can regulate populations of the foremost cassava pests . The principal natural enemies targeting cassava pests in SE Asia are listed in Table .…”
Section: Managementmentioning
confidence: 99%
“…Periodic releases of lacewings appear to be effective against T. urticae and T. kanzawai , but have not been evaluated in cassava crops . Lastly, entomopathogens can inflict high mortality on mites, and have received some attention for control of M. tanajoa , T. kanzawai , T. urticae and T. cinnabarinus on various crops, including cassava …”
Section: Managementmentioning
confidence: 99%